Transient Stability Analysis of the IEEE-9 Bus System under Multiple Contingencies - Anwar, N.; Hanif, A. H.; Khan, H. F.; Ullah, M. F. (Engineering, Technology & Applied Science Research, 2020)
The determination of the transient stability of an electric power system is a crucial step in power system analysis. This paper investigates the transient stability of an IEEE-9 bus system consisting of three generators and nine buses. At first, a load flow analysis is conducted in order to determine the pre-fault conditions. Secondly, fault analysis is performed to analyze post fault conditions like the fast fault clearing time and load switching in order to determine the system stability. For transient stability analysis, Euler and Runga methods are compared and applied on the frequency and rotor angle of the system to analyze the system variations under different fault conditions. The simulations were done on the Power World Simulator (PWS) software. It is concluded that Critical Fault Clearing Time (CFCT) is a very important factor in keeping the power system within the stability bounds. A slight increase in Clearing Time (CT) from the critical value causes un-synchronism.